Społeczne aspekty zarządzania projektem - Pietroń-Pyszczek, Agata; Trenkner, Małgorzata (Social Aspects of Project Management, 2009)
The aim of the paper is to present social problems occurring in project management. These problems were tackled in terms of organization, team and an individual. An attempt of presenting a 'profile' of a project team member and project manager was made, paying special attention to their social (soft) features. The description can help improve human resources management in projects. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 52, s. 424-430